(untitled) (New York, 1987)
This book is designed to guide you through the critical financial transitions of a lifetime: being single, getting married, getting divorced, saving for the children's education, preparing for retirement, building credit, investing money, using insurance to work for you, buying a home or car, planning your estate, paying taxes, and learning how to confidently plan your financial future.
Keywords: Finance, personal,Investments,Tài chính cá nhân